The abundance of molecular hydrogen and its correlation with midplane pressure in galaxies: non-equilibrium, turbulent, chemical models - Mac Low, Mordecai-Mark; Glover, Simon (The astrophysical journal, 2012)
Observations of spiral galaxies show a strong linear correlation between the ratio of molecular to atomic hydrogen surface density Rmol and midplane pressure. To explain this, we simulate three-dimensional, magnetized turbulence, including simpliﬁed treatments of non-equilibrium chemistry and the propagation of dissociating radiation, to follow the formation of H2 from cold atomic gas. The formation timescale for H2 is sufﬁciently long that equilibrium is not reached within the 20-30 Myr lifetimes of molecular clouds. The equilibrium balance between radiative dissociation and H2 formation on dust grains fails to predict the time-dependent molecular fractions we ﬁnd. A simple, time-dependent model of H2 formation can reproduce the gross behavior, although turbulent density perturbations increase molecular fractions by a factor of few above it. In contradiction to equilibrium models, radiative dissociation of molecules plays little role in our model for diffuse radiation ﬁelds with strengths less than 10 times that of the solar neighborhood, because of the effective self-shielding of H2. The observed correlation of Rmol with pressure corresponds to a correlation with local gas density if the effective temperature in the cold neutral medium of galactic disks is roughly constant. We indeed ﬁnd such a correlation of Rmol with density. If we examine the value of Rmol in our local models after a free-fall time at their average density, as expected for models of molecular cloud formation by large-scale gravitational instability, our models reproduce the observed correlation over more than an order-of-magnitude range in density.